2013
DOI: 10.3109/13693786.2012.698025
|View full text |Cite
|
Sign up to set email alerts
|

Fungal hemolysins

Abstract: Hemolysins are a class of proteins defined by their ability to lyse red cells but have been described to exhibit pleiotropic functions. These proteins have been extensively studied in bacteria and more recently in fungi. Within the last decade, a number of studies have characterized fungal hemolysins and revealed a fascinating yet diverse group of proteins. The purpose of this review is to provide a synopsis of the known fungal hemolysins with an emphasis on those belonging to the aegerolysin protein family. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 156 publications
(169 reference statements)
1
55
0
2
Order By: Relevance
“…Time-course studies performed for the expression of Asphemolysin and terrelysin have also showed that their expression is highest during early fungal growth (Nayak et al 2012;Wartenberg et al 2011). All of this suggests that these aegerolysins have important roles in fungal development (Berne et al 2009;Nayak et al 2013;Ota et al 2014; views of Aspergillus niger N402 mycelia (4 days old) and the filtrate (c) from minimal medium liquid culture after 2 or 3 days on tryptic soy agar supplemented with 5 % defibrillated sheep blood. Partial hemolysis is observed as the greenish agar around and underneath the colony and around the hole in the agar Vesper and Vesper 2004).…”
Section: Activities Of the Aegerolysin Proteinsmentioning
confidence: 98%
See 3 more Smart Citations
“…Time-course studies performed for the expression of Asphemolysin and terrelysin have also showed that their expression is highest during early fungal growth (Nayak et al 2012;Wartenberg et al 2011). All of this suggests that these aegerolysins have important roles in fungal development (Berne et al 2009;Nayak et al 2013;Ota et al 2014; views of Aspergillus niger N402 mycelia (4 days old) and the filtrate (c) from minimal medium liquid culture after 2 or 3 days on tryptic soy agar supplemented with 5 % defibrillated sheep blood. Partial hemolysis is observed as the greenish agar around and underneath the colony and around the hole in the agar Vesper and Vesper 2004).…”
Section: Activities Of the Aegerolysin Proteinsmentioning
confidence: 98%
“…niger (Braaksma et al 2010;Nayak et al 2012;Novak et al 2014). All this suggests that aegerolysin-like proteins are promising biomarkers for the detection of fungal exposure, especially in the case of opportunistic fungal infections (Nayak et al 2013).…”
Section: Biomarkers Of Fungal Exposurementioning
confidence: 98%
See 2 more Smart Citations
“…It belongs to the larger group of highly homologous proteins called aegerolysins (Pfam PF06355, InterPro IPR009413), currently comprising more than 350 entries in the NCBI databases. The structure, putative functional characteristics and occurrence of aegerolysins across the tree of life have been reviewed in details elsewhere [12,13]. OlyA/PlyB is specifically expressed during the formation of mushroom fruit bodies [7,14].…”
Section: Chemical Structure and Biological Propertiesmentioning
confidence: 99%